The Role of The Internet and Social Media in Transforming Youth Values - Ergashev Oybek Qaxramon o‘g‘li (Goodwood Publishing, 2026)
Purpose: This article aims to examine the impact of the internet and social media on youth values, focusing on cognitive, psychological, and social dimensions, and exploring the balance between opportunities and risks. Research Methodology: This study employs a mixed-method approach, including surveys, literature review, and empirical observation of youth social media usage in Uzbekistan between 2017 and 2025. Results: The findings indicate that social media enhances access to information, civic engagement, and global connectivity, but also presents challenges such as misinformation, addiction, and exposure to harmful content. Conclusions: Social media has a transformative effect on youth values, requiring careful management through media literacy and promotion of ethical online behavior to preserve cultural heritage, moral integrity, and national identity. Limitations: The study focuses primarily on Uzbek youth and does not include longitudinal tracking or experimental interventions, limiting generalizability. Contributions: This research contributes to understanding how digital technologies and social media shape youth values, providing insights for educators, policymakers, and researchers to foster responsible and culturally aware online engagement